A high-performance lithiated silicon–sulfur battery enabled by fluorinated ether electrolytes. Issue 45 (9th November 2021) - Zhang, Leicheng; Zhao, Chen; Lin, Yanke; Wu, Maochun; Zhao, Tianshou
Abstract : The newly developed fluorinated electrolyte enables the good cycling performance of lithiated silicon–sulfur batteries. Abstract : Lithiated silicon–sulfur (Si–S) batteries are an attractive energy storage system that can offer higher theoretical energy density and lower cost than current lithium-ion batteries. However, this type of battery using conventional ether electrolytes suffers from a short lifespan, resulting from poor anode stability and severe polysulfide shuttle effects. To tackle these challenges, here we report a fluorinated ether electrolyte to boost the performance of lithiated Si–S batteries. The newly developed electrolyte not only enables the formation of a robust solid-electrolyte interphase on the Si surface, which effectively accommodates volume variation, thus stabilizing the Si anode, but also leads to quasi-solid-state conversion of S species, thereby considerably mitigating the polysulfide shuttle effect. As a result, a Si–S full battery using the fluorinated electrolyte is able to deliver a high initial capacity of 902 mA h g −1 and maintain capacity retention of 64.0% after 100 cycles. By contrast, the capacity of a cell using conventional ether electrolyte rapidly decays to 162 mA h g −1, which is only 17.5% of its original value. More impressively, for the first time, we demonstrate that a full cell can operate stably with a high cathode loading (6.2 mg cm −2 ) and lean electrolyte (<10 μL mg −1 ), showing great potential for achieving high-performance and high-energy batteries.